Effects of physiotherapy combined with sirolimus in a patient with vascular malformation: A case report - Akbayrak, Türkan; Orhan, Ceren; Baran, Emine; Kaya, Serap; Coskun, Gürsoy; Varan, Ali (The Turkish Journal of Pediatrics, 2016)
The aim of the present case report was to investigate the effects of a physiotherapy program combined with sirolimus in a child patient with upper extremity edema and joint limitation due to low-flow vascular malformation. This case report included an 11-year-old male patient (26 kg, 130 cm) diagnosed with congenital lymphovascular malformation on the left and right chest. The patient, who had edema on the upper left extremity and experienced joint limitations, was administered complete decongestive therapy (CDT) and manual therapy in combination with sirolimus. Physiotherapy included a total of 24 sessions, 3 sessions a week for 8 weeks. Following the physiotherapy, the patient was assigned to a home therapy program, and then the maintenance phase of the CDT was initiated. Evaluations were carried out at baseline, at the end of week 8, and after 12 months. Following the physiotherapy program combined with sirolimus, a decrease in extremity volume, an increase in joint movement range, and an improvement in disease-related complaints were observed. Physiotherapy methods combined with sirolimus may be an effective treatment method in patients with vascular malformations. However, further studies with larger sample size are warranted.
Keywords: complete decongestive therapy; manual therapy; physiotherapy; sirolimus; vascular malformation